Aspek Biologi Ikan Ilisha Megaloptera di Sungai Bilah Sebagai Bahan Kuliah Mata Kuliah Zeologi Vertebrata (Bertulang Sejati) - Indah Purnama Sari; Khairul Khairul; Hasmi Syahputra Harahap (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to determine the biological aspects of the kemprit fish (Ilisha megaloptera) found in the Bilah River. The method used was exploratory, with fish sampling points determined based on fishing areas used by local fishermen (purposive sampling). The fishing gear used to catch the fish was a trap net. The total length and weight of the captured fish were measured. The results showed that fish sizes were classified into size classes, namely: small (43–51 cm) with a frequency of 6 individuals; (52–64 cm) with a frequency of 24 individuals; (65–73 cm) with a frequency of 8 individuals; medium (74–82 cm) with a frequency of 4 individuals; (83–91 cm) with a frequency of 7 individuals; and large (92–100 cm) with a frequency of 1 individual. In conclusion, the biological aspects of Ilisha megaloptera in the Bilah River are still considered very good. Keywords: Biological Aspects, Ilisha megaloptera, Bilah River